A starch-based composite material for a household compostable cosmetic bottle and a preparation method and application thereof
Patent Information
- Application Number
- CN202610660734.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-05-14
AI Technical Summary
[0003]然而,现有技术在同时满足上述多方面性能方面存在明显不足:一方面,以PLA为主体的硬质材料虽然刚性较好,但其在家庭堆肥环境中降解缓慢,且本身质地脆、抗冲击性差,限制了其在化妆品包装领域的广泛应用
本发明通过选择不含PLA的PBS/PBAT体系,并采用疏水改性淀粉、特定粒径的无机填料和成核剂等多重技术特征的组合,获得了一种在家庭堆肥条件下兼具高刚性、低水蒸气透过率和良好加工成型性的化妆瓶用淀粉基复合材料。具体如下:
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of biodegradable polymer materials for cosmetic packaging bottles, and particularly to a starch-based composite material for cosmetic bottles that is compostable at home, its preparation method, and its application. Background Technology
[0002] With increasing environmental awareness, the application of biodegradable materials in cosmetic packaging is receiving growing attention. Currently, common biodegradable materials mainly include polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), and starch-based materials. To address the needs of different waste disposal scenarios, certification standards for biodegradable materials have been subdivided into two major systems: industrial composting and home composting. Industrial composting is typically carried out under high temperature (58±2℃), high humidity, and strictly controlled conditions; while home composting is conducted in an environment with normal temperature (25±5℃), natural ventilation, and fluctuating humidity, requiring more stringent standards for material disintegration and degradation. However, most existing biodegradable materials are designed for industrial composting conditions, and generally suffer from slow degradation and incomplete disintegration in home composting environments. For example, polylactic acid degrades rapidly in industrial composting, but its degradation rate is extremely low, or even almost non-existent, under normal temperature home composting conditions. For rigid packaging containers such as cosmetic bottles, in addition to meeting compostability requirements, the materials must also possess sufficient rigidity, low water vapor permeability, good injection molding processability, and creep resistance at the threaded parts of the bottle neck (to prevent stripping and leakage after screwing on the cap). Furthermore, to increase the bio-based content, natural materials such as starch are often introduced.
[0003] However, existing technologies have significant shortcomings in simultaneously satisfying the aforementioned multiple performance requirements: On the one hand, while rigid materials based on PLA have good rigidity, they degrade slowly in home composting environments and are inherently brittle and have poor impact resistance, limiting their widespread application in cosmetic packaging. For example, although the PLA / wood composite material disclosed in CN113226755B has demonstrated its disintegration under industrial composting conditions, it has not yet addressed the disintegration performance under low-temperature environments such as home composting. On the other hand, while materials based on PBS or PBAT possess good flexibility and processability, achieving a balance between rapid disintegration and high rigidity in home composting environments has always been a technical challenge in this field. Furthermore, when starch is introduced into hydrophobic polyester systems, the hydrophilicity of starch leads to a significant decrease in the water-blocking performance of the composite material, and the interfacial compatibility issues between starch and polyester also weaken the material's mechanical properties.
[0004] Chinese patent CN118085527A discloses a fully biodegradable polymer material containing starch, PLA, and nanofillers. However, it is mainly composed of PLA, with extremely low nanofiller content (only 1-3 parts), relying primarily on PLA itself for rigidity, which fails to address the problem of slow PLA degradation in home composting. Chinese patent CN102295831A discloses a fully biodegradable material for rigid sheets, using PHA and PLA as a matrix and adding a certain amount of mineral fillers. However, this material still contains PLA and does not address its disintegration performance in home composting environments, nor does it solve the compatibility issue between starch and polyester.
[0005] Therefore, how to make PBS / PBAT-based composite materials possess high rigidity, low water vapor permeability, good injection molding performance and thread creep resistance under home composting conditions without PLA, while maintaining a high disintegration rate, has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a home compostable starch-based composite material for cosmetic bottles, which has the characteristics of home compostability, high rigidity, low water vapor transmission rate and good injection molding performance, as well as its preparation method and application.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a starch-based composite material for cosmetic bottles that is compostable at home, characterized in that it comprises the following raw materials by weight: 40-70 parts of biodegradable polyester, 20-40 parts of hydrophobically modified thermoplastic starch, 20-40 parts of inorganic filler, and 0.5-3 parts of nucleating agent. The biodegradable polyester is selected from at least one of polybutylene succinate and polybutylene adipate-terephthalate, and does not contain polylactic acid; the inorganic filler is selected from at least one of talc and calcium carbonate; the composite material has a flexural modulus ≥ 1.2 GPa, and a disintegration rate ≥ 90% within 12 weeks under home composting conditions (25±5℃).
[0008] Preferably, the amount of the inorganic filler is 25-35 parts.
[0009] In a preferred embodiment of the starch-based composite material for cosmetic bottles described in this invention, the hydrophobic modification is selected from one of esterification modification, etherification modification, and crosslinking modification.
[0010] As a preferred embodiment of the starch-based composite material for cosmetic bottles described in this invention, the hydrophobically modified thermoplastic starch is acetate-esterified starch with a degree of substitution of 0.2-0.8.
[0011] In a preferred embodiment of the starch-based composite material for cosmetic bottles according to the present invention, the average particle size D50 of the inorganic filler is ≤ 10 μm. Preferably, D50 is ≤ 5 μm.
[0012] In a preferred embodiment of the starch-based composite material for cosmetic bottles described in this invention, the nucleating agent is at least one of talc, hydrazide compounds, or organophosphate nucleating agents.
[0013] As a preferred embodiment of the starch-based composite material for cosmetic bottles according to the present invention, the composite material has a heat distortion temperature ≥ 80℃ under a load of 0.45 MPa; the water vapor transmission rate of the injection-molded sample of the composite material at 38℃ and 90% relative humidity is ≤ 15 g / (m²). 2 •24h).
[0014] As a preferred embodiment of the starch-based composite material for cosmetic bottles described in this invention, it further comprises at least one of the following additives: 1-5 parts compatibilizer, 3-10 parts plasticizer, 0.5-2 parts lubricant, 0.5-1.5 parts anti-hydrolysis agent, and 0.2-1 parts antioxidant.
[0015] Preferably, the compatibilizer includes, but is not limited to, maleic anhydride-grafted PBS or PBAT.
[0016] Preferably, the plasticizer includes, but is not limited to, glycerin, sorbitol, etc.
[0017] Preferably, the lubricant includes, but is not limited to, calcium stearate, zinc stearate, etc.
[0018] Preferably, the anti-hydrolysis agent includes, but is not limited to, carbodiimide.
[0019] Preferably, the antioxidants include, but are not limited to, 1010 and 168.
[0020] Secondly, the present invention provides a method for preparing the above-mentioned starch-based composite material for cosmetic bottles, comprising the following steps: S1. Mix the hydrophobically modified thermoplastic starch, inorganic filler, nucleating agent and optional additives evenly to obtain a premix; S2. The biodegradable polyester is mixed with the premix, melt-blended and extruded in a twin-screw extruder to obtain composite material granules.
[0021] Optionally, in step S1, the mixing is carried out in a high-speed mixer at a temperature of 10-60℃, a speed of 200-400 rpm, and a time of 5-15 min.
[0022] Optionally, in step S1, each component can be dried separately before mixing: the biodegradable polyester is vacuum dried at 70-90℃ for 3-6 hours, the hydrophobically modified starch is dried at 60-80℃ for 4-6 hours, and the inorganic filler is dried at 100-120℃ for 2-4 hours to remove moisture and prevent hydrolysis during processing.
[0023] Optionally, in step S2, the length-to-diameter ratio (L / D) of the twin-screw extruder is 36:1 to 48:1, the screw speed is 200-500 rpm, and the feeding speed is 10-30 kg / h.
[0024] Optionally, in step S2, the extrusion temperature is controlled in zones from the feed port to the die head as follows: 120-140℃, 140-160℃, 155-175℃, 165-185℃, 165-185℃, 160-180℃, 155-175℃, 150-170℃.
[0025] Preferably, the temperature of each zone can be fine-tuned according to the type of biodegradable polyester and the filler content. For example, when the PBAT content is high, the processing temperature can be appropriately reduced by 2-5℃.
[0026] Optionally, in step S2, a vacuum exhaust port can be set during the extrusion process to remove low molecular weight volatiles and moisture, and the vacuum degree is controlled at -0.06 to -0.08 MPa.
[0027] Thirdly, the present invention provides a cosmetic packaging bottle, which is made by injection molding using the above-mentioned starch-based composite material for cosmetic bottles or composite material granules prepared by the above-mentioned preparation method.
[0028] In a preferred embodiment of the cosmetic packaging bottle of the present invention, the cosmetic packaging bottle is a cream jar, powder box, or lotion bottle. Preferably, after applying a torque of 2 N·m to the threaded portion of the bottle neck at room temperature and maintaining it for 24 hours, the torque decay rate is ≤ 15%.
[0029] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention, by selecting a PLA-free PBS / PBAT system and employing a combination of multiple technical features including hydrophobically modified starch, inorganic fillers of specific particle sizes, and nucleating agents, yields a starch-based composite material for cosmetic bottles that exhibits high rigidity, low water vapor permeability, and good processability under home composting conditions. Details are as follows: The compostable starch-based composite material for cosmetic bottles of this invention comprises, by weight, the following raw materials: 40-70 parts of biodegradable polyester, 20-40 parts of hydrophobically modified thermoplastic starch, 20-40 parts of inorganic filler, and 0.5-3 parts of nucleating agent. By controlling the particle size D50 of the inorganic filler to ≤10μm, a modulus increase can be achieved at the stated filler amount. Simultaneously, the hydrophobically modified starch, filler, and polyester form a composite system. In a home composting environment, the starch component absorbs water, swells, and degrades, contributing to accelerated overall disintegration. Therefore, despite the presence of non-degradable filler, the overall disintegration rate of the material still meets home composting standards. Furthermore, limiting the filler dosage to 20-40 parts is a key range for achieving a balance between high rigidity and compostability. Adding nucleating agents can improve the crystallization rate and crystallinity of PBS / PBAT. On the one hand, it helps to increase the heat distortion temperature of the material under a load of 0.45MPa to above 80℃, meeting the heat resistance requirements of cosmetic bottles during filling, storage and transportation, and avoiding high-temperature deformation. On the other hand, it improves creep resistance, making the torque attenuation rate of the bottle mouth thread ≤15%, avoiding the problem of "cold flow" stripping.
[0030] This invention utilizes a PLA-free system and synergistic hydrophobic modified starch, achieving a disintegration rate ≥90% within 12 weeks under ambient home composting conditions (25±5℃). Simultaneously, the hydrophobic modified starch and inorganic filler create a barrier effect, resulting in a water vapor permeability (38℃, 90% RH) ≤15 g / (m³). 2 • 24h), effectively extending the shelf life of cosmetics. The composite material of this invention can be molded into thick-walled containers (cream jars, powder boxes, lotion bottles, etc.) using conventional injection molding processes, resulting in products with smooth surfaces and dimensional stability. The raw materials used do not contain PLA and are mainly derived from biomass, meeting environmental regulations and can replace traditional non-degradable plastics. It is particularly suitable for the cosmetic packaging field, which emphasizes environmental protection and home composting. Its heat distortion temperature is ≥80℃, making it suitable for cosmetic bottle products that need to withstand high-temperature filling or tropical storage and transportation environments, with broad application prospects. Detailed Implementation
[0031] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments. The embodiments described below are some, but not all, embodiments of this invention. The embodiments of this invention are used to illustrate the invention, not to limit it. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. Unless otherwise specified, experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer. The raw materials and reagents used are commercially available conventional products or products that conform to relevant national / industry standards and are all commercially available.
[0032] The cosmetic bottle described in this invention is a packaging bottle used to hold cosmetics (such as lotions, serums, creams, etc.).
[0033] Source of raw materials The raw materials used in the specific embodiments are all commercially available industrial products, and their specific sources and specifications are shown in the table below. Those skilled in the art can choose equivalent substitutes as needed, without being limited to specific brands or models.
[0034] Table 1
[0035] Terminology Explanation In this invention, PBS is polybutylene succinate, PBAT is polybutylene adipate-terephthalate, and PLA is polylactic acid. WVTR is water vapor transmission rate, and D50 is the average particle size (median volume particle size).
[0036] Example 1 This embodiment provides a compostable starch-based composite material for cosmetic bottles, with the following formula by weight: 60 parts of biodegradable polyester (PBS), 25 parts of hydrophobically modified thermoplastic starch (acetic acid esterified starch, degree of substitution 0.5), 25 parts of inorganic filler (talc, D50=5μm), 1 part of nucleating agent (TMC-306), 2 parts of compatibilizer (maleic anhydride grafted PBS), 5 parts of plasticizer (glycerol), 0.8 parts of lubricant (calcium stearate), 0.5 parts of anti-hydrolysis agent (carbodiimide), and 0.3 parts of antioxidant (antioxidant 1010).
[0037] This embodiment provides a method for preparing the above-mentioned composite material, and the specific steps are as follows: (1) PBS was vacuum dried at 80℃ for 4h, acetic acid-esterified starch was dried at 70℃ for 4h, and talc was dried at 105℃ for 2h; (2) Weigh the dried acetic acid esterified starch, talc, nucleating agent, compatibilizer, plasticizer, lubricant, anti-hydrolysis agent and antioxidant according to the proportion, put them into a high-speed mixer, and mix at 300 rpm for 8 minutes at room temperature to obtain a premix. (3) Mix the dried PBS with the premixed material evenly, add it to a twin-screw extruder (length-to-diameter ratio 40:1) for melt blending and extrusion granulation; extruder temperature: zone 1 130℃, zone 2 150℃, zone 3 165℃, zone 4 170℃, zone 5 175℃, zone 6 175℃, zone 7 170℃, zone 8 165℃, screw speed 300rpm, feeding speed 15kg / h, and vacuum exhaust (vacuum degree -0.07MPa) is turned on during the extrusion process. (4) The extruded strip is air-cooled and then cut into pellets to obtain composite material pellets, which are the starch-based composite material for cosmetic bottles that can be composted at home in this embodiment.
[0038] Example 2 The difference between this embodiment and Example 1 is that: 55 parts of biodegradable polyester (PBAT), 20 parts of hydrophobically modified thermoplastic starch (acetic acid esterified starch, degree of substitution 0.5), and 30 parts of inorganic filler (calcium carbonate, D50=3μm) are used.
[0039] The remaining components, proportions, and preparation methods are the same as in Example 1.
[0040] Example 3 The difference between this embodiment and Example 1 is that: a mixture of 45 parts PBS and 15 parts PBAT is used as the biodegradable polyester (60 parts in total); 30 parts of hydrophobically modified thermoplastic starch (acetic acid esterified starch, degree of substitution 0.5); 20 parts of inorganic filler (talc, D50=5μm); and 1 part of nucleating agent (TMC-306).
[0041] The remaining components, proportions, and preparation methods are the same as in Example 1.
[0042] Example 4 This embodiment provides a compostable starch-based composite material for cosmetic bottles, with the following formula by weight: 50 parts biodegradable polyester (PBS), 20 parts hydrophobically modified thermoplastic starch (acetic acid esterified starch, degree of substitution 0.5), 20 parts inorganic filler (talc, D50=5μm), 0.5 parts nucleating agent (TMC-306), 2 parts compatibilizer (maleic anhydride grafted PBS), 5 parts plasticizer (glycerol), 0.8 parts lubricant (calcium stearate), 0.5 parts anti-hydrolysis agent (carbodiimide), and 0.3 parts antioxidant (antioxidant 1010).
[0043] The remaining components, proportions, and preparation methods are the same as in Example 1.
[0044] Example 5 This embodiment provides a compostable starch-based composite material for cosmetic bottles, with the following formula by weight: 60 parts of biodegradable polyester (PBS), 40 parts of hydrophobically modified thermoplastic starch (acetic acid esterified starch, degree of substitution 0.5), 40 parts of inorganic filler (talc, D50=5μm), 3 parts of nucleating agent (TMC-306), 5 parts of compatibilizer (maleic anhydride grafted PBS), 10 parts of plasticizer (glycerol), 1.5 parts of lubricant (calcium stearate), 1.0 part of anti-hydrolysis agent (carbodiimide), and 0.6 parts of antioxidant (antioxidant 1010).
[0045] The remaining components, proportions, and preparation methods are the same as in Example 1.
[0046] Comparative Example 1 The difference between this comparative example and Example 1 is that the average particle size D50 of the inorganic filler (talc) is 20 μm (ordinary industrial grade), while the other components and proportions are the same as in Example 1.
[0047] The preparation method of this comparative example is the same as that of Example 1.
[0048] Comparative Example 2 The difference between this comparative example and Example 1 is that biodegradable polyester (PBS) is replaced with an equal amount of polylactic acid (PLA) (molecular weight approximately 150,000), while the remaining components and proportions are the same as in Example 1.
[0049] The preparation method of this comparative example is the same as that of Example 1.
[0050] Comparative Example 3 The difference between this comparative example and Example 1 is that "hydrophobically modified thermoplastic starch (acetic acid esterified starch)" is replaced with an equal amount of ordinary thermoplastic starch (unmodified, prepared from ordinary corn starch and glycerol plasticizer), while the remaining components and proportions are the same as in Example 1.
[0051] The preparation method of this comparative example is the same as that of Example 1.
[0052] Comparative Example 4 The difference between this comparative example and Example 1 is that the amount of inorganic filler (talc, D50=5μm) is 10 parts, and the amount of biodegradable polyester (PBS) is increased to 75 parts; the remaining components and proportions are the same as in Example 1.
[0053] The preparation method of this comparative example is the same as that of Example 1.
[0054] Comparative Example 5 The difference between this comparative example and Example 1 is that the amount of inorganic filler (talc, D50=5μm) is 50 parts, and the amount of biodegradable polyester (PBS) is reduced to 35 parts (to keep the total amount approximately the same); the remaining components and proportions are the same as in Example 1.
[0055] The preparation method of this comparative example is the same as that of Example 1.
[0056] The comparative example encountered processing difficulties such as poor melt flowability, unstable feeding, and filler agglomeration on the surface of the injection molded parts during the preparation process. The specific test results are shown in Table 3.
[0057] Comparative Example 6 The difference between this comparative example and Example 1 is that the inorganic filler is replaced with an equal amount of calcium carbonate, and the nucleating agent TMC-306 is not added; the remaining components and proportions are the same as in Example 1.
[0058] The preparation method of this comparative example is the same as that of Example 1.
[0059] Performance testing 1. Sample preparation and testing The composite material granules prepared in Examples 1-5 and Comparative Examples 1-5 were dried at 80°C for 2 hours, and then injection molded into standard test specimens (bending specimens, tensile specimens) and cosmetic packaging bottles (cream jars, including threaded bottle necks) using an injection molding machine. Injection molding process: barrel temperature 165°C, mold temperature 30°C, injection pressure 100MPa, holding pressure 60MPa, cooling time 20s.
[0060] The obtained samples were numbered as follows: Sample A (Example 1), Sample B (Example 2), Sample C (Example 3), Sample D (Example 4), Sample E (Example 5), Sample F (Comparative Example 1), Sample G (Comparative Example 2), Sample H (Comparative Example 3), Sample I (Comparative Example 4), Sample J (Comparative Example 5), and Sample K (Comparative Example 6).
[0061] 2. Testing Methods The performance test items, methods, and standards are shown in Table 2 below.
[0062] Table 2
[0063] Note: The disintegration rate test for home compost is conducted according to AS 5810-2010 "Biodegradable Plastics for Home Composting". A 50mm × 50mm × 2mm injection-molded sample (the sample thickness is comparable to the typical wall thickness of a cosmetic bottle) is buried in a simulated home compost medium composed of mature compost, fresh fruit and vegetable waste, and garden waste in a specific ratio. Under conditions of 25±5℃ and 50-60% humidity, the sample is turned over every 7-10 days. After 12 weeks, the sample is removed, cleaned, dried, and weighed to calculate the disintegration rate. Disintegration rate = (initial mass - mass after 12 weeks) / initial mass × 100%.
[0064] In heat distortion temperature testing, the specimen dimensions are prepared according to standard requirements. If no standard specimen is available, an injection-molded bending specimen can be used for direct testing.
[0065] 3. Test Results The above performance tests were performed on the AK samples, and the test results are shown in Table 3 below.
[0066] Table 3
[0067] 4. Test Result Analysis Based on the data in Table 3, Examples 1-5 of the present invention exhibit excellent and balanced characteristics in all key performance indicators: their flexural modulus is not less than 1.28 GPa (with Examples 1 and 5 reaching 1.45 GPa and above), meeting the rigidity requirements of cosmetic bottles; their heat distortion temperature is all above 84℃ (≥80℃); and their water vapor transmission rate is all below 15 g / (m²). 2 • 24h), with good barrier properties; at the same time, all embodiments can meet the disintegration rate standard for home composting (≥90%), and the processing torque attenuation rate is controlled within 10%, showing excellent processing stability.
[0068] Further analysis of Table 3 revealed that: Example 4 (20 parts filler, flexural modulus 1.28 GPa) had a disintegration rate of 92%, Example 1 (25 parts filler, flexural modulus 1.58 GPa) had a disintegration rate of 93%, and Example 5 (40 parts filler, flexural modulus 1.45 GPa) had a disintegration rate of 90%. It is evident that within the filler content range of 20-40 parts, lower filler content resulted in a modulus ≥1.2 GPa and a higher disintegration rate, while higher filler content increased the modulus to 1.58 GPa and maintained a disintegration rate ≥90%. This achieved a good balance between rigidity (flexural modulus ≥1.2 GPa) and the disintegration rate of home compost (≥90%), with both ends of the formulation meeting the standards, demonstrating the rationality and criticality of the component range.
[0069] In contrast, the comparative examples failed to simultaneously meet the comprehensive requirements of rigidity, barrier properties, disintegration resistance, and processability due to factors such as missing components (e.g., Comparative Example 6 lacked a nucleating agent), the introduction of incompatible components (e.g., Comparative Example 2 contained PLA), or improper proportions (e.g., Comparative Example 4 had too low a filler content, and Comparative Example 5 had too high a filler content). This indicates that the components and proportions defined in this invention have a synergistic effect and are key to achieving good overall performance.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A starch-based composite material for compostable cosmetic bottles, characterized in that, The product contains the following raw materials by weight: 40-70 parts of biodegradable polyester, 20-40 parts of hydrophobically modified thermoplastic starch, 20-40 parts of inorganic filler, and 0.5-3 parts of nucleating agent; The biodegradable polyester is selected from at least one of polybutylene succinate and polybutylene adipate-terephthalate, and does not contain polylactic acid; the inorganic filler is selected from at least one of talc and calcium carbonate; the average particle size D50 of the inorganic filler is ≤ 10 μm; the flexural modulus of the composite material is ≥ 1.2 GPa, and the disintegration rate is ≥ 90% within 12 weeks under home composting conditions of 25±5℃.
2. The starch-based composite material for cosmetic bottles as described in claim 1, characterized in that, The hydrophobic modification is selected from one of esterification modification, etherification modification, and crosslinking modification.
3. The starch-based composite material for cosmetic bottles as described in claim 1, characterized in that, The hydrophobically modified thermoplastic starch is acetate-esterified starch with a degree of substitution of 0.2-0.
8.
4. The starch-based composite material for cosmetic bottles as described in claim 1, characterized in that, The nucleating agent is at least one of talc, hydrazide compounds, or organophosphate nucleating agents.
5. The starch-based composite material for cosmetic bottles as described in claim 1, characterized in that, The composite material exhibits a heat distortion temperature ≥ 80℃ under a load of 0.45 MPa; the water vapor transmission rate of the injection-molded sample of the composite material at 38℃ and 90% relative humidity is ≤ 15 g / (m²). 2 •24h).
6. The starch-based composite material for cosmetic bottles as described in claim 1, characterized in that, It also contains at least one of the following additives: 1-5 parts compatibilizer, 3-10 parts plasticizer, 0.5-2 parts lubricant, 0.5-1.5 parts anti-hydrolysis agent, and 0.2-1 part antioxidant.
7. A method for preparing a starch-based composite material for cosmetic bottles as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Mix the hydrophobically modified thermoplastic starch, inorganic filler, nucleating agent and optional additives evenly to obtain a premix; S2. The biodegradable polyester is mixed with the premix, melt-blended and extruded in a twin-screw extruder to obtain composite material granules.
8. A cosmetic packaging bottle, characterized in that, The composite material granules are prepared by injection molding using the starch-based composite material for cosmetic bottles as described in any one of claims 1 to 6 or the preparation method described in claim 7.
9. The cosmetic packaging bottle according to claim 8, characterized in that, The cosmetic packaging bottles are cream jars, powder boxes, or lotion bottles.
Citation Information
Patent Citations
A fully biodegradable rigid sheet material and its preparation method
CN102295831A
Compostable wood composites
CN113226755B
Full-biodegradable high polymer material and preparation method thereof
CN118085527A
Fully-biodegradable plastic resin
CN102311617A
Biodegradable polyester composition and use thereof
US20210061989A1